Kualitas Hidup Keluarga dengan Balita dalam Pencegahan Stunting Melalui Psikoedukasi - Suwarno Suwarno; Nur'Aini Purnamaningsih; Muhammad Erwan Syah; Ita Suryani; Lidwina Daru Andani; Niken Wijayanti; Mila Savitri (Pancanaka, 2022)
The family is the smallest unit of society whose needs for mental and physical health will be seen as a family as a context, client, component of the society and system. These four elements are highly considered by health workers, families, communities and the government when identifying, formulating problems, and implementing policy strategies. This study to determine the quality life of families with toddlers in preventing stunting through psychoeducation. This research was a quasi-experimental research. Measurement of the level of quality of life using the SF-36. The sample in this study were families with toddlers in Bener Yogyakarta village. The results showed that there was an increase in the quality of life of families with children under five before and after psychoeducation with the lowest score post psychoeducation 73.86 on the dimension of social function and the highest on physical function 91.75. While the quality of life component was increased with the highest score in the physical component of 82.00. There is the improvement of the quality life of families with toddlers significantly before and after psychoeducation. Psychoeducation can be applied and continued in broader research to prevent stunting disease in terms of family mental health.